Pengelolaan Supervisi Pembelajaran Di Sd Negeri Tuban 1 Gondangrejo Karanganyar - Abadi, Zaenal; , Prof.Dr. Abdul Ngalim,M.M.,M.Hum; , Dr, Ahmad Muhibbin.M,.Si (2016)
The purpose of this study, there are three, (1) Describe the planning supervision SDN learning in Tuban I ndangrejo Karanganyar, (2) Describe the implementation of instructional supervision in Tuban I Gondangrejo Karanganyar SDN, and (3) Describe the feedback meeting instructional supervision in Tuban I Gondangrejo aranganyar SDN. This research is a qualitative research design is ethnographic research. Data collection techniques used in this study is observation, interview and documentation. Data analysis techniques in this study using an interactive model of data collection, data reduction, data presentation, and conclusion. The results showed that teacher supervision rotated in accordance with the sequence number of personnel (DUK). Video recording equipment installed before the children were in class. Assessment was made the principal aspects in the form of a score and description. evaluation results can be used as feedback to establish an effort to improve quality of education. The results of the meeting feedback shows that teachers are lacking using innovative methods and the use of props.